2014
DOI: 10.1109/tgrs.2013.2244214
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Uncertainties in Land-Surface Microwave Emissivity Retrievals

Abstract: Abstract-Uncertainties in the retrievals of microwave land surface emissivities were quantified over two types of land surfaces: desert and tropical rainforest. Retrievals from satellite-based microwave imagers, including SSM/I, TMI and AMSR-E, were studied. Our results show that there are considerable differences between the retrievals from different sensors and from different groups over these two land surface types. In addition, the mean emissivity values show different spectral behavior across the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…This issue is more highlighted in desert areas due to moisture scarcity and minimal vegetation interferences. These results are consistent with a previous study by Tian et al (2014) in terms of systematic differences at various frequencies. Also, a wider gap can be noticed between the average monthly emissivity values in the horizontal and vertical polarizations over desert.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This issue is more highlighted in desert areas due to moisture scarcity and minimal vegetation interferences. These results are consistent with a previous study by Tian et al (2014) in terms of systematic differences at various frequencies. Also, a wider gap can be noticed between the average monthly emissivity values in the horizontal and vertical polarizations over desert.…”
Section: Resultssupporting
confidence: 94%
“…The study of Tian et al (2014) accounted for random and systematic errors using statistical approaches and suggested that the differences among retrievals are caused likely by cloud or rain contaminations.…”
mentioning
confidence: 99%
“…These results confirm the previous studies, with the largest differences being observed over snow cover regions and deserts [ Prigent et al , ; Ferraro et al , ; Ringerud et al , ; Tian et al , ]. Note that these surface types correspond not only to large discrepancies between modeled and satellite‐derived emissivities but also to significant variability among models and among sources of satellite‐derived emissivities [ Ferraro et al , ].…”
Section: Emissivity Comparisonsmentioning
confidence: 99%
“…They pointed out that the emissivity at horizontally polarized 19 GHz can decrease to 0.8 because of prior heavy precipitation events or irrigated lands, which significantly wet the surface. Such a phenomenon, that is, that vegetation is able to depolarize the emissivity relative to bare soil, has been realized by numerous studies (e.g., Brunfeldt and Ulaby 1986;Tian et al 2013). Prigent et al (1997Prigent et al ( , 1998 investigated the MLSE at continental and global scales also using SSM/I data under clear sky.…”
Section: Introductionmentioning
confidence: 97%
“…Yang and Weng (2011) showed that the land surface temperature is the primary source of error in emissivity estimation for frequencies lower than 19 GHz. By evaluating several MLSE datasets, Tian et al (2013) demonstrated that there exist large discrepancies among the estimates from different sensors and from different investigators for the same targeted region. Results showed that the differences between day and night emissivities are reduced to less than 0.01 by integrating such a lookup table.…”
Section: Introductionmentioning
confidence: 99%